Unveiling Strategy of Developing Bank Waqf in Indonesia - Fuad, Iwan Agustiawan; Patria Yunita (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2024)
This study aims to present an alternative to the current banking system, namely through the optimization of the cash waqf concept and its management within a waqf bank framework. This study uses the Partial Least Square Structural Equation Model (PLS SEM) with several assumptions related to the structure and operational system of the bank used, using a survey of 114 respondents from banking practitioners, regulators and waqf practitioners. In this study, variables used include capital contribution, credit security, ownership structure, margin, legal status and transaction agreements on the waqf bank structure. Empirical findings are based on the views of waqf administrators. The results of the analysis conclude that capital contribution and transaction agreement models affect the structure of waqf banks in Indonesia. Meanwhile, credit security, form of ownership, margin and legal status do not significantly affect the structure of waqf banks in Indonesia. This study is expected to help the development of waqf banks in Indonesia. This study can contribute to the effectiveness of institutions for the poor and society. These implications are not limited to a particular country. Charitable organizations and the poor in every society will benefit from this study if the idea of​​total social banking is implemented. This study is a pioneer study in empirically addressing the structure and operation of waqf banks in Indonesia.